Coping and adaptation and their relationship to the spiritual perspective in patients with HIV/AIDS. - Pérez Giraldo, Beatriz; Veloza Gómez, Mónica del Mar; Ortiz Pinilla, Jorge Eduardo (Investigación y Educación en Enfermería, 2012)
Objective. To identify the coping and adaptation process and its relationship to the spiritual perspective in patients with HIV/AIDS. Methodology. Cross-sectional descriptive study in which 100 patients participated and who were applied instruments like Roy’s coping and adaptation measurement scale and Reed’s Spiritual Perspective Scale. The study was conducted in 2009, at a state healthcare institution in Bogotá (Colombia). Results. Five patient subgroups were identified (Recursive and Centered, Physical and Focused, in warning process, in systematic processing, and knowing and relating) who presented different dynamics regarding the greater or lesser use of coping strategies. In most patients a high spiritual perspective was identified upon the experience of the disease. A weak, but significant correlation was found between the coping and adaptation processes and the components of the spiritual perspective. Conclusion. A relationship exists between the spiritual perspective and the coping and adaptation process to the HIV/AIDS disease; the aforementioned must be considered in the therapeutic relationship as a relevant component of caretaking.